National analysis of urinary cadmium concentration and kidney stone: Evidence from NHANES (2011–2020) - Ye, Zhenyang; Chen, Zaizhi; Luo, Jinyang; Xu, Lijing; Fan, Dongping; Wang, Jia (Frontiers in Public Health, 2023)
Background: The association between urinary cadmium and kidney stone is inconsistent in previous studies, needing further exploration. To explore the association between urinary cadmium and kidney stone, this study was preformed. Materials and Methods: Data from the National Health and Nutrition Examination Survey (2011–2020) were included and further analyzed. Urinary cadmium was stratified into quartiles with quartile 1 (Q1: 0.025 0.104 μg/L) and quartile 4 (Q4: 0.435 7.581 μg/L). Further weighted logistic regression was adopted to evaluate the association between urinary cadmium and kidney stone. Subgroup analysis was used to verify the findings. The non-linear association was examined using the restricted cubic spline (RCS) regression. Results: A total of 9,056 adults aged 20 years and above was included in this study. In the fully adjusted model, an increased risk of kidney stone was identified for quartile 2 (OR = 1.40, 95% CI = 1.06-1.84, P < 0.05), quartile 3 (OR = 1.18, 95% CI = 0.88-1.59, P > 0.05), and quartile 4 (OR = 1.54, 95% CI = 1.10-2.06, P < 0.05). Similar association was found between continuous cadmium increase and OR of kidney stone in the full model (OR = 1.13, 95% CI = 1.01-1.26, P < 0.05). The RCS non-linear association also noted a non-linear association between urinary cadmium concentration and kidney stone risk (P for nonlinear < 0.001). Conclusion: In summary, cadmium exposure is identified as a risk factor for kidney stone in this study. Their non-linear association makes demands on early intervention for cadmium exposed population. Medical interventions for kidney stone prevention should take cadmium exposure into account.